Which Is a Better Predictor of GFR Decline: 24-h Urine Protein or 24-h Protein–Creatinine Ratio? An Exploration of the MDRD Study Data - Ayoub, Isabelle; Nagaraja, Haikady N.; Kang, Rima; Rovin, Brad; Bhatt, Udayan (Frontiers in Nephrology, 2022)
Background: Proteinuria is a known risk factor for progression of chronic kidney disease. Proteinuria magnitude can be estimated by measuring spot urine protein to creatinine ratio (least accurate), 24 hr urine collection for protein (24P) or 24 hr protein creatinine ratio (24 PCR). The MDRD study found that 24 P measured at baseline was the strongest single predictor of the rate of GFR decline during study follow up. However, predictive powers of 24P and 24 PCR have not been compared in the literature. The current study addresses this question using the MDRD cohort data. Methods: The study is a retrospective analysis of prospectively collected data from the MDRD cohort using simple and multiple regression models. Slope of measured GFR (mGFR) over time was used as the response and models that included baseline 24 PCR or 24 P were compared for the entire sample and for subgroups formed by restricting the values of 24 hour creatinine and 24 P. Results: Log 24 P and Log 24 PCR correlated almost equally with mGFR slope. However in simple linear regression models and multivariable linear regression models adjusting for age and sex, the model with 24 PCR had a higher R2 than the corresponding one that had 24P except for the subgroup 24 P<1g. Conclusion: We observe that 24 PCR may be a better marker of proteinuria magnitude in predicting decline in kidney function compared to 24 P in particular for patients with 24 P ≥1. This finding needs validation in prospective clinical trials.